Without compass or map cultural organizations, different dialogues - Katyal, Anjum; Kishore, Naveen (Seagull Books, 2004)
An attempt to highlight dialogues on traditional, contemporary arts, socio-economic and media in the form of cultural exchange among seven Asian countries.